Utilization of Waste Glass in Concrete - Tamanna, N.; Mohamed Sutan, N.; Lee, D.T.C; Yakub, I. (ENCON 2013, 2013)
The amount of waste glass has gradually increased over the recent years due to urbanization and industrialization where most of the waste glass end up in landfill while only small fraction can be recycled because of the high cost of cleaning and colour sorting. Since glass is not biodegradable, landfill is not an environmentally friendly solution. Recent studies have shown that the waste glass can be effectively used in concrete either as aggregate (fine or coarse aggregate) or as cement replacement. Being amorphous and containing relatively large quantities of silicon and calcium, glass is in theory pozzolanic or even cementitious in nature when the particle size is less than 75 micron. Finely ground glass as oppose to coarse waste glass does not contribute to alkali-silica reaction. Besides improving the properties of concrete by pozzolanic reaction by partial replacing the cement will contribute to a greener environment for the production of one ton of Portland cement produces about one ton of carbon dioxide leading to global warming issues. This paper gives an overview of the current progress and recycling situation of waste glass and point out the direction for the proper use of waste glass as replacement of cement. These will not only help in the reuse of waste glass but also create a greener environment.